DEVELOPMENT TRENDS OF YOUTH TOURISM IN UZBEKISTAN: PROBLEMS AND PROSPECTS (Marketing Journal, 2025)
This article examines the current state and key development drivers of youth tourism in Uzbekistan. Particular attention is given to the evolving preferences of young travelers, the growing impact of digital platforms such as Airbnb, and the rising popular ity of adventure tourism. The study is supported by the results of a survey conducted among 128 respondents, providing a basis for practical recommendations aimed at enhancing the youth tourism sector.
Keywords: Youth tourism; adventure tourism; digital platforms; tourism; tourism innovators